Why do you choose to teach Chinese as a second language? A study of pre-service CSL teachers’ motivations - Zhang, Haiwei; Jinjin Wu; Yong Zhu (System, 2020)
Many countries are facing a shortage of modern language teachers, including teachers of Chinese as a second language (CSL), which is believed to relate to pre-service teachers’ motivations. Thus, this study aims to explore pre-service CSL teachers’ motivations and the background variables that might influence their motivations. The participants were 411 pre-service CSL teachers. A 33-item questionnaire adopted from the Factors Influencing Teaching Choice (FIT-Choice) scale was administered, including nine FIT-Choice subscales and two new subscales. First, exploratory factor analysis of data from the first random split-half sample of participants suggested a 6-factor structure, which was confirmed in the subsequent confirmatory factor analysis of data from the second random split-half sample of participants. The results show that pre-service CSL teachers had strong intrinsic value, cross-cultural value and altruistic value but weak extrinsic value. Second, structural equation modelling analysis was performed with questionnaire data from 296 participants who provided complete demographic information. Age, annual family income and frequency of contact with foreigners significantly predicted the participants’ motivations, yet their predictive power varied. The implications for understanding the theoretical framework of teacher motivation and the professional development of CSL teachers were discussed.
Keywords: Expectancy-value theory; FIT-Choice scale; Individual differences; Language teacher motivation; Teachers of Chinese as a second language